Carving a professional identity : the occupational epigraphy of the Roman Latin West - Varga, Rada (Archaeopress Roman archaeology, 2020)
This volume presents the results of long-term research into occupational epigraphy from the Latin-language provinces of the Roman Empire. It catalogues stone epigraphs of 690 independent professionals (excluding state workers, imperial slaves, freedmen and military personnel) providing quantitative as well as qualitative analyses of the raw data